Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $$A_r=\int_{{0}}^{\frac{\pi}{2}} \sin^{r}x \ \ dx$$
What is the relation beween $A_r$ and $A_{r-2}$ ? Then, find the value of $A_r$ for all $r$.

share|cite|improve this question
First write: $A_r = \int_0^{\pi /2} (1 - \cos^2 x) \cdot \sin^{r-2} x \, dx = A_{r-2} - \int_0^{\pi/2} \cos^2 x \, \sin^{r-2} x \, dx$ and for integration by parts take: $u = \cos x, \; v' = \cos x \, \sin^{r-2} x$. – qoqosz Jun 10 '12 at 16:09
Answer to your question is here. – Amihai Zivan Jun 10 '12 at 17:12
up vote 1 down vote accepted

Assume $r\ge 2$. To integrate by parts, let $u=\sin^{r-1} x$, $dv=\sin x\,dx$. Then $du=(r-1)\cos x\,\sin^{r-2}x\,dx$ and we can take $v=-\cos x$. So we find that $$A_r=\left.(-\cos x)\sin^{r-1} x\right|_0^{\pi/2}+\int_0^{\pi/2}(r-1)\cos^2 x \sin^{r-2} x\,dx.$$

Since $r \ge 2$, the first term on the right-hand side is $0$ (the cosine term dies at $\pi/2$, the sine term dies at $0$). Rewrite $\cos^2 x$ as $1-\sin^2 x$. Then we obtain $$A_r=\int_0^{\pi/2}(r-1)(1-\sin^2 x)\sin^{r-2} x\,dx=(r-1)A_{r-2}-(r-1)A_r.$$ From this we obtain $$rA_r=(r-1)A_{r-2},\quad\text{or equivalently}\quad A_r=\frac{r-1}{r}A_{r-2}.\tag{$1$}$$

Now for an integer $r$ there are $2$ quite different cases, $r$ odd and $r$ even. Treat them separately.

After a while, you will be able to find a general formula. But note that our recurrence $(1)$ gives $A_r$ in terms of the "simpler" $A_{r-2}$. Then we can use the recurrence to express $A_{r-2}$ in terms of the simpler $A_{r-4}$, and so on. I suggest you first handle the cases $r=1$, and $r=0$. For example, it is easy to verify that $A_1=1$.

Now let's deal with odd $r$. It is best to deal first with a concrete case. Let's for example find $A_7$. By the recurrence $(1)$, we have $A_7=\frac{6}{7}A_5$. But again by recurrence $(1)$, $A_5=\frac{4}{5}A_3$. But $A_3=\frac{2}{3}A_1$. So $A_7=\frac{6}{7}\cdot\frac{4}{5}\cdot\frac{2}{3}$.

Now you should be able to see what happens in the general case $r$ odd.

For $r$ even, go through a similar procedure for say $r=6$ or $r=8$ to see what's going on. Then you should be able to handle the general case.

share|cite|improve this answer
10x for help, I will try to solve the rest. – nour Jun 10 '12 at 19:19
For $r$ is odd, I got this general equation by reccurrence $A_r=\frac{r-1}{r}.\frac{r-3}{r-2}.\frac{r-5}{r-4}. \dots .\frac{r-7}{r-6}$ but for example if I plug in $r$=3 in this general equation I will get zero as an answer...similarly for other values of $r$...I don't know where is my mistake...any help? thanks – nour Jun 10 '12 at 20:59
You just have to know when to stop. It is the product $\prod_{i=0}^{(r-1)/2} \frac{r-2i-1}{r-2i}$. You can also write it as a product in the other direction, starting at the right end. – André Nicolas Jun 10 '12 at 21:10

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.